Sexual and physical abuse and its determinants among street children in Addis Ababa, Ethiopia 2016 - Ayana Chimdessa; Amsale Cheire (BMC, 2018)
Abstract Background The life and health of street children is becoming a global concern. Street children are vulnerable to a variety of problems including physical, psychological and sexual exploitations as well as social isolation. Therefore, it was the purpose of this study to point out the experience of sexual and physical exploitation and its determinant factors among street children in Addis Ababa, the capital city of Ethiopia. Methodology A phenomenological qualitative method was conducted from March to June 2016 in Addis Ababa, Ethiopia. Data were collected from street children by focus group discussion (FGD) and in-depth interview. Open code was used to analyze data. The transcribed note was translated. Following this coding was done. Based on a coding book, major themes and main categories were developed and analyzed. Result The study has explored the life experience of street children in the city. Deaths of parents/unhealthy relationship of extended families forced them be on a street. Thus, flee to street to search for work was the main reason for joining to a street. Street children are vulnerable to sexual and physical exploitations on a daily basis. For street children, street is the world characterized by misery deprivation, physical, verbal and sexual abuse and become daily victims of violence. There is no safe place for the children of on-street. Most street children are involved in all types of sex; heterosexual, bisexual, homosexual and group sex are common among themselves and out siders. They are involved highly in transactional sex for survival. Drug use, stress and depression are common experiences. Thus, they were socially isolated. The main challenges of living on a street are lack of basic needs, social isolation, lack of safety and security and being out of school are the common problems these vulnerable groups are facing. Conclusions Street children are at high risk of sexual and physical exploitation. Interventions targeting integration and reunion with families, reduction of physical and sexual exploitation, access to education, mental health promotion and reduction of drug use behavior should be taken in to considerations.